Pengaruh Kepercayaan, Keamanan Dan Kemudahan Pengguna Terhadap Keputusan Transaksi Digital Pada E-Wallet (Studi Pada Mahasiswa Prodi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Pengguna Aplikasi Ovo) - Rohman, Kholilur; Khalikussabir, Khalikussabir; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to test and determine the influence of trust, security and user convenience on digital transaction decisions on e-wallets (Study on Management Study Program Students, Faculty of Economics and Business, Islamic University of Malang, Users of the OVO Application). This research is a type of quantitative research. The sampling technique used Malhotra's formula with calculated results of 85 samples. To solve the problems in this research, SPSS was used with validity tests, reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heteroscedasticity tests, F tests, and t tests. The research results show that simultaneously the variables Trust (X1), Security (X2), and Convenience (X3) have a significant effect on Transaction Decisions (Y). Partial research results show that Trust (X1), Security (X2) and Convenience partially have a significant effect on Transaction Decisions. Keywords: Trust, Security, Convenience, Transaction Decisions.